Joan of Arc - Poole, Josephine; Barrett, Angela (New York : A.A. Knopf, 1998)
A biography of the fifteenth-century peasant girl who led a French army to victory against the English, witnessed the crowning of King Charles VII, and was later burned at the stake for witchcraft.
Maps on endpapers.
Wilson's Children.
Elem. School Library Collection.
Notable/Best Books (A.L.A.).
4.2
3-6
Keywords: Joan, -- of Arc, Saint, -- 1412-1431 -- Pictorial works -- Juvenile literature; Joan, -- of Arc, Saint, -- 1412-1431.; Joan, -- of Arc, Saint, -- 1412-1431.; Christian saints -- Biography. -- Juvenile literature; Hundred Years War, 1339-1453 -- Pictorial works -- Juvenile literature; Saints; Women -- Biography; Christian saints -- Biography; Women -- Biography; Christian saints; Hundred Years' War, 1339-1453.; Saints; Women -- Biography; France -- History -- Charles VII, 1422-1461 -- Pictorial works -- Juvenile literature; France -- History -- Charles VII, 1422-1461.; France -- History -- 1328-1589, House of Valois; France -- History -- Charles VII, 1422-1461.